2019
DOI: 10.5194/angeo-2019-62
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semimonthly oscillation observed in the start time of equatorial Spread-F

Abstract: Abstract. Using data from airglow an all sky imager and a coherent backscatter radar deployed at São João do Cariri (7.4° S, 36.5° W) and São Luís (2.6° S, 44.2° W), respectively, the start time of equatorial Spread-F were studied. Data from a period of over 10 years was investigated from 2000 to 2010. The semimonthly oscillations were clearly revealed in the start time of plasma bubbles from Oi6300 airglow images during three periods (September 2003, September–October 2005, November 2005 and January 2008). Si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…In addition to nonmigrating diurnal tides, Paulino et al (2019) have shown the start time of EPBs displaying a semimonthly oscillation. They suggested that the quasi 16‐day planetary waves and lunar semidiurnal tide may control either the start time of EPBs or the amplitude of the PRE, providing additional evidence that lower atmospheric forcing contributes to the day‐to‐day variability of EPBs.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…In addition to nonmigrating diurnal tides, Paulino et al (2019) have shown the start time of EPBs displaying a semimonthly oscillation. They suggested that the quasi 16‐day planetary waves and lunar semidiurnal tide may control either the start time of EPBs or the amplitude of the PRE, providing additional evidence that lower atmospheric forcing contributes to the day‐to‐day variability of EPBs.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Besides the planetary waves, there is growing evidence that the lunar semidiurnal tides have a great importance in the generation of spread F (e.g., Paulino et al, 2019). Using OI 630 nm all-sky imaging and coherent backscatter radar in the equatorial region over South America, Paulino et al (2019) observed that a semimonthly oscillation due to quasi 16 days planetary waves and lunar semidiurnal tide can modulate the PRE responsible to generate ionospheric irregularities. Figure 1b shows a map with the GPS-TEC stations used to study the distance between adjacent plasma bubbles (also referred as interbubble distance).…”
Section: 1029/2019ja027441mentioning
confidence: 99%
“…They showed that ultrafast Kelvin waves in the mesosphere-low thermosphere region could modulate the vertical drift and explain the oscillations observed in the ionospheric parameters. Besides the planetary waves, there is growing evidence that the lunar semidiurnal tides have a great importance in the generation of spread F (e.g., Paulino et al, 2019). Using OI 630 nm all-sky imaging and coherent backscatter radar in the equatorial region over South America, Paulino et al (2019) observed that a semimonthly oscillation due to quasi 16 days planetary waves and lunar semidiurnal tide can modulate the PRE responsible to generate ionospheric irregularities.…”
Section: 1029/2019ja027441mentioning
confidence: 99%
“…Em se tratando da transfusão de sangue, a tomada de decisão é impactante, podem emergir dilemas éticos relacionados à transfusão sanguínea em pessoas com restrições religiosas, devido ao desejo dos enfermeiros de salvar uma vida e ao mesmo tempo de respeitar a autonomia desses frente à possibilidade de optar em não ser transfundido (SOUZA, 2014). As enfermeiras desvelam conflitos e dilemas éticos quando se deparam com situações de doações de órgãos, Na discussão acerca da doação de órgãos há um conflito de consciência que emerge de pensamentos sobre a finitude e sua relação com o corpo após a morte; o que desperta para inúmeras questões éticas por envolver a autonomia e os direitos dos pacientes (PAULINO;TEIXEIRA, 2009). No tocante a vivência de casos em que o prognóstico é ruim e que precisa obedecer as recomendações para evitar a distanásia, as enfermeiras ressaltam que os aspectos éticos devem ser respeitados, ao tempo que revelam que alguns procedimentos cirúrgicos acabam por prolongar a vida da pessoa por muitos anos.…”
Section: [] Muitas Vezes Passamos Batido Em Perguntar a Família Se El...unclassified